Association between retinal vein occlusion and an increased risk of acute myocardial infarction: A nationwide population-based follow-up study. - Yu-Yen Chen; Shwu-Jiuan Sheu; Hsiao-Yun Hu; Dachen Chu; Pesus Chou (PLoS ONE)
Objective To investigate a possible association between retinal vein occlusion (RVO) and an increased risk of developing acute myocardial infarction (AMI). Design A population-based retrospective cohort study using the entire population of the Taiwan National Health Insurance Research Database (NHIRD) from 1st January, 2001 to 31st December, 2013. Methods A total of 37921 subjects with RVO were enrolled in the RVO group, and 113763 subjects without RVO were enrolled in the comparison group. The comparison group consisted of randomly selected individuals who were propensity score (PS)-matched with the RVO group at a ratio of 1:3, based on age, gender, obesity, stroke, hyperviscosity syndrome, glaucoma, and the use of antithrombotic drugs. A log-rank test was used to compare the cumulative hazard of AMI between the two groups. A multivariate Cox regression analysis was used to estimate the adjusted hazard ratios (HRs) of AMI, adjusted for PS, diabetes, hypertension, hyperlipidemia, congestive heart failure, and chronic renal failure. Results The mean age of the cohort was 62.4±13.2 years. RVO patients had significantly higher proportions of diabetes, hypertension, hyperlipidemia, congestive heart failure, and chronic renal failure than the comparisons. The mean follow-up period was 5.52 years in the RVO group and 5.55 years in the comparison group (p = 0.16). A log-rank test comparing the cumulative hazard curves of AMI for the two groups revealed a significant difference (p<0.0001). In the multivariate Cox regression after adjustment for PS and confounders, the RVO group had a significantly higher risk of AMI (adjusted HR = 1.21; 95% CI: 1.13 to 1.30). When the RVO group was divided into central retinal vein occlusion (CRVO) and branch retinal vein occlusion (BRVO) and analyzed separately, both groups had significantly higher adjusted HRs for developing AMI than the comparison group. Moreover, the CRVO group had a significantly higher risk of AMI than the BRVO group. Conclusions People with RVO are at significantly greater risk of developing AMI than individuals without RVO.